A prediction model of atrial fibrillation recurrence after first catheter ablation by a nomogram: HASBLP score - Han, Wenqiang; Liu, Yan; Sha, Rina; Liu, Huiyu; Liu, Aihua; Maduray, Kellina; Ge, Junye; Ma, Chuanzhen; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2022)
Background: At present, catheter ablation is an effective method for rhythm control in patients with atrial fibrillation (AF). However, AF recurrence is an inevitable problem after catheter ablation. To identify patients who are prone to relapse, we developed a predictive model that allows clinicians to closely monitor these patients and treat them with different personalized treatment plans. Methods: 1065 patients who underwent AF catheter ablation between January 2015 and December 2018 were consecutively included in this study, which examines the results of a 2-year follow-up. AF patients were divided into development cohort and validation cohort. Univariate and multivariate analysis were carried out on the potential risk factors. Specific risk factors were used to draw the nomogram according to the above results. Finally, we verified the performance of our model compared with CHADS2 and CHA2DS2-Vasc scores by Receiver Operating Characteristic curve and calibration curve and plotted the DAC curve. Results: A total of 316 patients experienced AF recurrence. After univariate and multivariate analysis, AF history (H), age (A), snoring (S), BMI (B), anteroposterior diameter of LA (L), persistent AF (P) were included in our prediction model. Our model showed better performance compared with CHADS2 and CHA2DS2-Vasc score, the area under ROC curve (95% CI) was 0.7668(0.7298-0.8037) vs 0.6225 (0.5783-0.6666) and 0.6267 (0.5836-0.6717). Conclusion: We established a nomogram (HASBLP score) for predicting AF recurrence after the first catheter ablation at a 2-year follow-up, which can be used as a tool to guide future follow-up of patients. However, its usefulness needs further validation.